THE EFFECT OF CHICKEN FEET GELATIN TO CHARACTERISTIC OF JELLY CANDY - Miskiyah Miskiyah; Juniawati Juniawati; Nur Afni Oktafia; Siti Chairiyah Batubara (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
Jelly candy is a soft textured candy processed with hydrocolloid components such as gum, pectin, agar, starch, carrageenan, gelatin. These are used to modify the chewy texture. This study aimed was to determine the effect of the combination of chicken feet gelatin and agar on the quality of jelly candy. Processing of chicken feet gelatin jelly candy based on Caeccar et.al (2018) method by modification. The study used a completely randomized design (CRD) with one factor, five levels and three replications. The factors studied were the ratio of chicken feet gelatin and agar 80:20; 60:40; 40:60; 20:80; 0:100. Product quality characteristics observed in this study were water content, ash content, reducing sugar content, sucrose content, and organoleptic quality. The results showed that the combination of chicken feet gelatine and agar were significantly affected water, ash, reducing sucrose content. Jelly candy with a treatment combination of 80% chicken feet gelatine and 20% agar was the best treatment. The results of the analysis of the candy were water content of 11.02± 0.04%, ash content of 0.89± 0.00%, reducing sugar content of 10.83± 0.01%, sucrose content of 50.68± 0.28%. The organoleptic test results showed that chicken feet gelatine improved the texture and taste of jelly candy.